Relationship between platelet-to-lymphocyte ratio and Coronary Artery Lesion in non-diabetic patients with coronary heart disease. - Han, Maohua; Sun, Yaning; Li, Na (Journal of the Pakistan Medical Association, 2022)
This study was conducted to investigate the relationship between platelet-to-lymphocyte ratio and coronary artery lesion in non-diabetic patients with coronary heart disease. This observational research was done at Changyi people's Hospital, China, from January 2017 to August 2020. A total of 237 non-diabetic cases with suspected coronary heart disease were selected as subjects. Patients with negative coronary angiography were labelled as non-coronary heart disease patients (control group), patients with coronary heart disease confirmed on angiography comprised the coronary heart disease group. The results showed that smoking and hypertension history in the two groups were different (P =0.031 and 0.001). Platelet-to-lymphocyte ratio value and Gensini score in coronary heart disease group were higher as against the control group (both P<0.001). Platelet-to-lymphocyte ratio was an independent risk factor for coronary heart disease (P < 0.001) using logistic regression analysis. A significant positive correlation between platelet-to-lymphocyte ratio and Gensini score in coronary heart disease patients (r=0.510, P<0.001) was determined by spearman analysis. In conclusion, platelet-to-lymphocyte ratio can be acquired simply and quickly from blood routine examination, and its level is related to coronary artery lesion. Platelet-to-lymphocyte ratio may provide certain reference value in judging coronary artery lesion in non-diabetic patients with coronary heart disease. Key words: Non-diabetic; platelet-to-lymphocyte ratio; lymphocyte; coronary artery lesion